2005
DOI: 10.1021/cg049716m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Pressure on the Crystal Structures of Polymorphs of Glycine

Abstract: The effect of high pressure on the crystal structures of -, -and -glycine has been investigated. A new polymorph, δ-glycine, is obtained from  glycine. δ-Glycine is monoclinic, P2 1 /a, a = 11.156(4), b = 5.8644(11), c = 5.3417(17) Å,  = 125.83(4)° at 1.9 GPa. The transition, which occurs between 0 and 0.8 GPa, proceeds from a single crystal of -glycine to a single crystal of δ-glycine, resulting in an equal number of NH…O hydrogen bonds, but an increase in the number and strength of CH…O hydrogen bonds,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
293
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(313 citation statements)
references
References 67 publications
16
293
2
2
Order By: Relevance
“…Compressibility of cavities of biopolymers, the contribution of the rigidity of the cavity to the conformational stability of the biopolymer can also be mimicked by studying structures of smaller molecules (Boldyreva, 2006). Attempts were made to describe the anisotropic compression of some of the crystalline amino acids by 'closing voids' (Dawson et al, 2005;Moggach, Allan, Morrison et al, 2005;Moggach, Allan, Clark et al, 2006;Moggach, Marshall & Parsons, 2006). Although any pressure-induced process can be expected to result in a structure with a higher density and smaller voids, crystalline amino acids are still not the best systems to study compression of cavities since their properties are to a large extent determined by dipole-dipole interactions and strong hydrogen bonds (OHÁ Á ÁO and NHÁ Á ÁO).…”
Section: Compression Of the Same Phasementioning
confidence: 99%
“…Compressibility of cavities of biopolymers, the contribution of the rigidity of the cavity to the conformational stability of the biopolymer can also be mimicked by studying structures of smaller molecules (Boldyreva, 2006). Attempts were made to describe the anisotropic compression of some of the crystalline amino acids by 'closing voids' (Dawson et al, 2005;Moggach, Allan, Morrison et al, 2005;Moggach, Allan, Clark et al, 2006;Moggach, Marshall & Parsons, 2006). Although any pressure-induced process can be expected to result in a structure with a higher density and smaller voids, crystalline amino acids are still not the best systems to study compression of cavities since their properties are to a large extent determined by dipole-dipole interactions and strong hydrogen bonds (OHÁ Á ÁO and NHÁ Á ÁO).…”
Section: Compression Of the Same Phasementioning
confidence: 99%
“…[35][36] Here, we look to understand the influence of one-dimensional confinement on API polymorphism. We show controllable polymorphism in glycine and acetaminophen through applying the solution shearing method to these molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Data can give us some insights related to the behaviour of molecules of proline as the crystal is compressed. For example, in a previous study on -glycine, the softening of a bending of CO 2 -was associated to a decrease in the intra-layer hydrogen bond strength, while the stiffening of the same vibration was associated to an increase in the bond strength (Dawson et al, 2005). For PM we have observed that the band associated to both bending of CO 2 -, (CO 2 -), and rocking of CO 2 -, r(CO 2 -), increase wavenumbers from 1.1 to 6.5 GPa, and between 6.5 and 7.8 GPa decrease wavenumber; for (CO 2 -) the decreasing is represented by the two dashed lines in Figure 3 between the spectra of 6.5 and 7.8 GPa.…”
Section: L-proline Monohydratementioning
confidence: 93%
“…In fact, for other amino acid crystals it has been reported that the r(CO 2 -) is the most intense band in the 200 -700 cm -1 spectral range. However, for the other amino acids, differently from L-proline, the r(CO 2 -) mode is observed for wavenumber higher than 500 cm -1 (-glycine: 503 cm -1 (Dawson et al, 2005); L-alanine: 532 cm -1 ; L-valine, 542 cm -1 (Goryainov et al, 2005); DL-alanine, 543 cm -1 ; etc.). Finally, in the spectrum taken at 0.0 GPa we can observe a band at 574 cm -1 which was associated to a bending of CO 2 -, group.…”
Section: L-proline Monohydratementioning
confidence: 98%
See 1 more Smart Citation